Minorisations ordinaires dans l’enseignement supérieur.L’expérience d’étudiantes portant un hijab dans les Bouches du Rhône - Renaud Cornand; Pauline Delage (Genre, Sexualité et Société)
Prohibiting university students from wearing a hijab is regularly debated in the public sphere. Yet these students, as adult users of public higher education, have the right to wear them. Although universities and other French higher education institutions are technically spaces “open” to women who wear a hijab, they do not protect them from stigmatization and discrimination. This article focuses on the logics of marginalization and othering at play in higher education and some of their social effects. These women not only experience micro-aggressions and symbolic violence, but they often anticipate potential stigmatization and discrimination. Therefore, they adjust their behaviors and educational trajectories to avoid the negative experiences as much as possible. This article is based on 30 interviews conducted with students, between 20 and 30 years old, who live in Marseille and are enrolled in higher education curricula, either at universities or in social work schools. These interviews shed light on: 1) the specific relationship they have with higher education; 2) the types of symbolic violence and micro-aggressions they experience; 3) the risks of exclusion and discrimination they continually face.